Gas Tracer Techniques to Investigate Arctic Ocean Dynamics - Arck, Yannis (2024)
A multifarious ocean sampling campaign in the Arctic Ocean was carried out in summer 2021. The participating project Ventilation and Anthropogenic Carbon in the Arctic Ocean (VACAO) has the goal to investigate oceanic processes by combining a broad set of gaseous tracers. Water samples were taken at six distinct locations, resolving the complete water column from the surface to the ocean floor. Samples were analyzed for stable noble gas isotopes and the four age dating tracers argon-39, carbon-14, sulfur hexafluoride and chlorofluorocarbon-12. Special emphasis is given to the subsequent measurement and analysis techniques of noble gases and argon-39. Possible sampling and gas extraction methods of argon-39 for Atom Trap Trace Analysis are presented regarding applications to other environmental systems. The VACAO measurement results are interpreted individually and discussed in detail. Two developed models further process the tracer data generating a more complex insight into ocean dynamics. Noble gases are investigated concerning water mass formation and surface processes causing saturation anomalies. Transit time distribution modeling is applied to the four dating tracers to resolve age differences between the studied ocean basins and sampled water depths.